Integration Between Electronic Auditing and Accounting Information Systems and Their Role in Improving the Quality of Financial Statements - Jabbar Fashakh, Mohammed; Abdul-Ali Karim, Abbas (Iraqi Journal for Administrative Sciences, 2026)
This study aims to examine the impact of integrating electronic auditing with accounting information systems on improving the quality of financial statements. It explores the relationship between the adoption of modern auditing technologies and the efficiency and reliability of accounting information. The digital transformation has reshaped the business environment, compelling organizations to implement advanced accounting information systems capable of processing data with accuracy and speed, alongside electronic auditing methods that match the scale and complexity of such data. The findings indicate that the integration of electronic auditing and accounting information systems contributes to achieving higher levels of accuracy and transparency in financial reporting, enhancing the reliability of financial statements, and increasing investor and regulatory confidence. Moreover, it accelerates audit processes, reduces human errors, and improves the ability to detect risks and fraud through advanced analytical tools. This integration ultimately strengthens the quality of financial information, making it more relevant for sound economic and financial decision-making. The study concludes that such integration represents a fundamental pillar of corporate governance, supporting organizational sustainability and enabling institutions to cope with the challenges of the digital business environment.